A Study on Variations of Branching Pattern of Hepatic Arteries with its Clinical Significance - Mansur, D. I.; Karki, S.; Shrestha, A.; KC, B. (Kathmandu University Medical Journal, 2020)
Background Variation of hepatic artery is very frequent and may predispose the patients to inadvertent injury to the vessels during hepato-billiary surgery. With the advancement of new diagnostic, therapeutic and operative techniques for abdomen, the sound knowledge of variations of hepatic arterial system have become increasingly important for dealing clinicians, surgeons and interventional radiologists.Objective To study the variations of hepatic artery and to evaluate the possible clinical significances.Method A total of 104 images of abdominal computed tomography scans were used for this study. The origin and branching patterns of hepatic artery were recorded. After collecting the data, statistical analysis was done.Result The present study concluded that normal branching pattern of hepatic artery was seen in 86.54% cases, whereas 13.46% cases showed different types of variations. Among them, type II and IV pattern were seen in 0.96% in each, type VI in 1.93%, type VII in 2.87% and the most common variation type IX was seen in 3.85%. There were not a single case of type III, V, VIII and X recorded in this study. Addition to these, one of the variants was common hepatic artery originating from abdominal aorta, was seen in 1.93% of cases while the other variant is unnamed artery arising from superior mesenteric artery, was seen in 0.96% of cases.Conclusion The knowledge of the branching pattern of hepatic artery might be helpful for clinicians to the better understanding of the arterial supply of the liver and may reduce the risk of complications.